P693 Neisseria gonorrhoeae in-vitro susceptibilities to ceftriaxone, cefixime and azithromycin in GISP isolates, 1987–2017. (14th July 2019) - Kersh, Ellen; Kang, Jospeh; Dorji, Tandin; Pham, Cau; Schlanger, Karen; Cyr, Sancta St
Abstract : Background: In-vitro susceptibility distributions to antibiotics can evolve over time because of emerging resistance determinants. This can affect clinical drug efficacy and interpretation of laboratory susceptibility tests. In January 2019, the Clinical Laboratory Standards Institute (CLSI) analyzed Neisseria gonorrhoeae (Ng) susceptibility parameters for ceftriaxone (CRO), cefixime (CFX) and azithromycin (AZI) to review interpretive criteria for laboratory tests. Methods: GISP (Gonococcal Isolate Surveillance Project) is a United States national surveillance project at approximately 25 sentinel STD clinics, collecting about 5, 000 yearly urethral isolates from symptomatic men. From 1987–2017, minimal inhibitory drug concentrations (MIC) of 164, 506 isolates were determined by agar dilution using CLSI-recommended protocols. Susceptibility parameters were calculated with R software, and included mean MIC, 98.5% MIC indicating end of wild-type distribution, and percent isolates meeting 2019 CLSI susceptibility (S) criteria (CRO, CFX, AZI <= 0.25, 0.25, 1 μg/mL, respectively) or current GISP alert definitions (CRO, CFX, AZI ≥=0.125, 0.25, 2 μg/mL, respectively). Results: Since 1987, only 5 isolates did not meet CRO S criteria. CRO alerts peaked at 1.05% in 1991. Mean MICs were highest in 2016 (0.013 μg/mL; 95% CI: 0.013–0.013), but compared to the mean MIC when GISP began (0.011 μg/mL; 95% CI: 0.010–0.011) the difference was less than a full drug dilution. Isolates not meeting CFX S criteria, 76 since 1987, were at a 0.17% peak in 1992, as were mean MICs. Isolates not meeting AZI S criteria were highest at 3.6% and 4.4% in 2016 and 2017, respectively, as were mean MICs. Conclusion: Ng CRO and CFX in-vitro susceptibilities have not uniformly decreased since GISP began, while most indicators suggest declining AZI in-vitro susceptibility. CLSI reviewed these data in conjunction with clinical, pharmacokinetic/-dynamic and other international susceptibility data and kept steady (CRO, CFX) or established new (AZI) 2019 laboratory testing susceptibility criteria. Disclosure: No significant relationships.